(untitled) (Journal of Academic Research, 2026)
This research aims to explore the impact of organizational culture on organizational innovation at Misrata University, with a particular focus on identifying the cultural dimensions most influential in fostering innovative practices. To achieve this objective, the study adopted a descriptive-analytical approach. Data were collected through a questionnaire distributed to a random sample of 130 employees at the university, allowing for an analysis of the existing cultural environment and its support for the innovation process within the academic institution. The results revealed a strong and statistically significant positive correlation between the dimensions of organizational culture and innovation. These dimensions accounted for 42.8% of the variance in the level of organizational innovation. While "collaboration culture" emerged as the most prevalent element within the university environment, the study indicated a deficiency in "incentive culture." This necessitates the development of reward and incentive systems to support creative initiatives and activate the roles of autonomy and calculated risk-taking within the workplace.